Antioxidant Activity Of Ethanol Extract Of Papaya Leaves (Carica Papaya L.) On Reducing Blood Glucose Levels Of Streptozotocin-Induced Male Rats - Islamiati, Utami; Matra Novalia Palipadang; Almawati Podomi; Viola Putrika Alvinita Landu (Jurnal EduHealth, 2024)
The purpose of this study was to determine the content and total amount of secondary metabolites and determine the antioxidant activity and the effect of ethanol extract of papaya leaves on glucose reduction induced by streptozotocin in male albino rats. Measurement of the total content of secondary metabolites and antioxidants was carried out using a UV-visible spectrophotometer using DPPH reagent, and 30 male albino rats were divided into 6 groups, with 3 groups as normal controls. The negative control group received the appropriate dose: 100 mg/kgBB, 200 mg/kgBB, and 300 mg/kgBB. Positive qualitative test results include secondary metabolites such as alkaloids, flavonoids, saponins, and tannins. Quantitative test results show a total alkaloid content of 0.4739% (equivalent to quinine), saponins 7.518% (equivalent to sapogenin), tannins 0.147% (equivalent to tannic acid), and flavonoids 1.653% (equivalent to quercetin). The IC50 result of the antioxidant activity of papaya leaf extract of 83.07 ppm is included in the strong category. Blood glucose measurement data showed that ethanol extract from papaya leaves effectively reduced blood sugar levels with an average value of 106 mg/dl at a dose of 100 mg/kg body weight.